Zinc y cobre como marcadores biológicos y su correlación con la actividad enzimática en el Infarto Agudo de Miocardio - Silva Silva, Pamela Alejandra (2022)
ABSTRACT: Worldwide, there is high mortality from acute myocardial infarction due to the lack of early identification. In addition, there has been a diversity of criteria for diagnosing this health problem in recent years, some focusing on biomarkers. This research project aimed to analyze the correlation between zinc and copper as biomarkers with enzymatic activity in acute myocardial infarction. This study was supported by several inductive, deductive, analytical, and synthetic methods. The approach of this research was quantitative because it was correlational. The scope was descriptive because it was limited to describing existing information; logically, its design was non-experimental, of a retrospective cross-sectional type because data collection was carried out at a single point in time. The techniques used were literature review and indirect observation since the study was developed under theoretical foundations. The population consisted of 300 digital documents, including scientific articles, books, literature reviews, and doctoral theses found in the main databases. The sample consisted of 106 papers. Zinc and copper as biomarkers correlate with enzyme activity in acute myocardial infarction because, in this disease, there is a decrease in zinc and an increase in copper in the blood. There is also an increase in troponin (cTnT), creatine kinase (CK-MB mass), and cardiac muscle enzymes released into the blood after cardiac damage, which, when found at high levels, represent cardiovascular problems.